2016
DOI: 10.1039/c6cp00722h
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent density functional theory beyond Kohn–Sham Slater determinants

Abstract: When running time-dependent density functional theory (TDDFT) calculations for real-time simulations of non-equilibrium dynamics, the user has a choice of initial Kohn-Sham state, and typically a Slater determinant is used. We explore the impact of this choice on the exchange-correlation potential when the physical system begins in a 50 : 50 superposition of the ground and first-excited state of the system. We investigate the possibility of judiciously choosing a Kohn-Sham initial state that minimizes errors w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 42 publications
1
55
0
Order By: Relevance
“…We note that v p,kin (x) has a well from the peak in v (−) s [n GS ](x). The peak in v p,XC (x) has the same origin [28,29,30,31] and it nearly cancels the well in v p,kin (x). This cancelation is not exact and the fine features in We turn off the electron-electron interaction in the system by setting λ = 0.…”
mentioning
confidence: 90%
“…We note that v p,kin (x) has a well from the peak in v (−) s [n GS ](x). The peak in v p,XC (x) has the same origin [28,29,30,31] and it nearly cancels the well in v p,kin (x). This cancelation is not exact and the fine features in We turn off the electron-electron interaction in the system by setting λ = 0.…”
mentioning
confidence: 90%
“…For dn a step can be found that becomes steeper with increasing correlation in the system. This feature translates to different functionals of the density, and corresponds to the full real-space behavior of steps and peaks in the exact xc potential [23][24][25][26]. In QEDFT we have besides the electron-electron correlations also electron-photon correlations.…”
Section: Introductionmentioning
confidence: 99%
“…The electron that transfers now has its "own" KohnSham orbital, not tied to an electron that remains, so the orbitals in principle need not become delocalized over time. There is the question of adiabatic TDDFT making errors from the very start, as this uses a ground-state xc functional to describe an initially excited state, however the error from this effect can be relatively small when the initial Kohn-Sham configuration is chosen close to that of the exact wavefunction [137,146]. In fact, real simulations of photo-induced processes often begin with the Kohn-Sham system initially excited (e.g.…”
Section: B the Best That An Adiabatic Approximation Can Domentioning
confidence: 99%
“…For cases involving more than two electrons, or with two electrons in an initial Kohn-Sham state chosen to involve more than one orbital, an iterative method must be used to find the exact xc potential; Refs. [134,[137][138][139][140][141] contain examples.…”
Section: A Non-adiabatic Step Featuresmentioning
confidence: 99%